CURRENT SITUATION OF HUMAN RESOURCE TRAINING MANAGEMENT AT THE REHABILITATION AND OCCUPATIONAL DISEASE TREATMENT HOSPITAL, HO CHI MINH CITY (Vietnam Journal of Community Medicine, 2026)
Background: The increasing demand for healthcare and rehabilitation services in the context of population aging requires healthcare professionals to engage in continuing medical education (CME) and regularly update their professional competencies.Objective: To describe the current status of human resource training management at the Rehabilitation and Occupational Disease Treatment Hospital, Ho Chi Minh City, in 2023.Methods: A descriptive cross-sectional study was conducted among 161 physicians working at the hospital. Data were collected through retrospective review of training records and reports in 2023, along with structured interviews with training management staff.Results: In 2023, only 47.2% of physicians participated in CME activities, while 52.8% did not participate or were not granted CME certificates. The proportion of physicians achieving ≥48 CME credits was very low (0.6%). Although 75% of doctors reported having sufficient knowledge after training, only 25% felt fully confident in their professional practice.Conclusion: The management of continuing medical education at the hospital remains limited, as reflected by low participation rates and inadequate fulfillment of CME requirements. Strengthening management, developing context-appropriate training plans, and integrating training with clinical practice may help improve professional capacity and the quality of healthcare services.
Keywords: Continuing medical education; health human resources; rehabilitation.